UPAYA MENINGKATKAN KEMAMPUAN MEMBACA BAHASA DAERAH GORONTALO MENGGUNAKAN MODEL PROBLEM-BASED LEARNING (PBL) PADA PESERTA DIDIK KELAS III SDN 11 KOTA BARAT KOTA GORONTALO - Indra Ibrahim; Yulanti S. Mooduto; Yane Hardiyanti Mahmud (Jurnal Ilmu Pendidikan UMGo, 2025)
This classroom action research aims to improve students' ability to read Gorontalo local language texts through the Problem-Based Learning model in grade III of SDN 11 Kota Barat, Gorontalo City. The problem underlying this study was the low reading ability and learning participation of students in local language learning. The research was conducted in three cycles, and each cycle consisted of planning, action, observation, and reflection. The subjects were 12 grade III students, consisting of four male students and eight female students. Data were collected through observation, documentation, and oral reading tests that assessed fluency, pronunciation, voice clarity, intonation, and comprehension of text meaning. The data were analyzed using descriptive qualitative and quantitative techniques. The findings show that students' reading ability increased after the implementation of Problem-Based Learning. In the initial observation, only 2 students or 16.66% reached the mastery criteria. In Cycle I, 6 students or 50% reached mastery. In Cycle II, 10 students or 83.33% reached mastery. In Cycle III, all 12 students or 100% reached mastery. These results indicate that Problem-Based Learning encourages students to read more actively, discuss problems in texts, connect local language materials with their cultural context, and improve their confidence in reading Gorontalo local language texts.